Periodontal status in morbidly obese patients with and without obstructive sleep apnea syndrome risk: A cross-sectional study - Sales-Peres, Silvia H. C.; Groppo, Francisco C.; Rojas, Lida V.; Sales-Peres, Matheus De C. [UNESP]; Sales-Peres, Arsenio (Wiley, 2016)
Background: This cross-sectional study aims to investigate the correlation between obstructive sleep apnea syndrome (OSAS) risk with periodontal disease and anthropometric measures in Class III obese patients. Methods: Anthropometric measurements were taken from 108 patients of both sexes, aged 30 to 60 years. The Berlin questionnaire (Bq) and the Epworth sleepiness scale (ESS) were applied to determine the risk for OSAS. Full-mouth periodontal status was determined by probing depth, clinical attachment level, gingival bleeding index, and the presence of calculus. Unpaired Student t, x2, Fisher exact, and Mann-Whitney U tests were applied to analyze the differences between high and low risk for OSAS groups. Results: Overall, 81.5% of the patients showed high risk for OSAS, 46.3% had excessive daytime sleepiness, 41.5% were positive for both the Bq and ESS, and 97.2% had periodontal disease (periodontitis = 85.2% and gingivitis = 60.2%). Patients with periodontal disease showed high risk for OSAS (82.9%) and ESS (45.7%). However, there was no influence of periodontal disease on OSAS risk. Periodontitis was not associated with the ESS (odds ratio [OR] = 1.84, 95% confidence interval [CI] = 0.54 to 6.26) or Bq (OR = 0.87, 95% CI = 0.10 to 7.84), nor was gingivitis associated with the ESS (OR = 1.25, 95% CI = 0.48 to 3.25) or Bq (OR = 0.23, 95% CI = 0.03 to 1.84). Waist circumference (P = 0.03), neck circumference (NC, P <0.001), and the percentage of predicted NC (PPNC, P <0.001) were significantly larger in the patients at high risk for OSAS than in those at low risk for OSAS. Daytime sleepiness was also associated with NC (P = 0.02) and PPNC (P = 0.02). Conclusion: There was no association between periodontal disease and OSAS risk in Class III obese patients, but OSAS risk was associated with both NC and PPNC.
Keywords: Obesity Morbid; Periodontal Diseases; Sleep Apnea Syndromes